Detection performance analysis of advanced direction time lightning detection system in China - Zhu, Hualiang; Pang, Wenjing; Chen, Fengjiao; Zhang, Miaomiao; Wang, Jing; Wang, Zhichao (Frontiers in Earth Science, 2024)
In order to study the detection performance of the Advanced Direction Time Lightning Detection System (ADTD) over mainland China, the relationship between the detection efficiency (DE) and distance for ADTD sensor is analyzed using lightning location data by ADTD during 2014-2020, which fits well with the probability density function of the Gamma distribution. The DE and location accuracy of ADTD across China are hereafter evaluated according to the constructed probability density function. The results show that the DE of a single sensor first increases rapidly and then decreases slowly with the increase of the detection distance, and the model constructed based on the probability density function of Gamma distribution can explain this relationship well. In the regions with dense sensors such as central and eastern China, the DE of ADTD can reach 95%, with the majority of regions having lower location errors (less than 1000 m). While, in the areas where sensors are sparse such as the Qinghai-Tibet Plateau and at the edge of ADTD, the DE of ADTD is less than 90% (in some areas it is even lower than 50%), and the location error greater than 1000 m. In general, ADTD can accurately detect cloud-to-ground lightning events in most areas of China, but its accuracy is limited in some areas due to sparse sensors and instrument parameter settings.